2002
DOI: 10.1046/j.1365-2958.2002.03088.x
|View full text |Cite
|
Sign up to set email alerts
|

Iron transport and regulation, cell signalling and genomics: lessons from Escherichia coli and Pseudomonas

Abstract: Fig. 3.Organization and evolutionary traits of surface signalling systems of P. aeruginosa and C. crescentus. A. Organisation of fecI (black arrow), fecR (grey arrow) and fecA (white arrow) homologues in the P.aeruginosa (PA) and C. crescentus (CC) genomes. Annotations are according to the P. aeruginosa and C. crescentus genome databases (www.pseudomonas.com and www.tigr.org respectively). Genes (not to scale) are oriented according to the direction of transcription. B. Co-evolution of the iron starvation sigm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
259
1
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(267 citation statements)
references
References 79 publications
3
259
1
4
Order By: Relevance
“…Interestingly, the microarray analysis revealed that expression of the gene encoding the iron-regulated sigma factor PvdS was increased 11-fold in the rsmA mutant compared to wild-type. The fact that PvdS levels were increased in the rsmA mutant may explain the increase in expression of the pvd genes (Beare et al, 2003;Visca et al, 2002) but not the pch operon. Transcription of pchABCDE and fptA is activated by the AraC-like regulator PchR in the presence of pyochelin and repressed in the absence of pyochelin (Heinrichs & Poole, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the microarray analysis revealed that expression of the gene encoding the iron-regulated sigma factor PvdS was increased 11-fold in the rsmA mutant compared to wild-type. The fact that PvdS levels were increased in the rsmA mutant may explain the increase in expression of the pvd genes (Beare et al, 2003;Visca et al, 2002) but not the pch operon. Transcription of pchABCDE and fptA is activated by the AraC-like regulator PchR in the presence of pyochelin and repressed in the absence of pyochelin (Heinrichs & Poole, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…The production of siderophores is a metabolically costly process that is tightly regulated to ensure that production only occurs when siderophores are needed (24,39,67). One mechanism that bacteria use to regulate siderophore production is by controlling expression of the siderophore production genes via an extracytoplasmic function (ECF) factor (39,67). The siderophore produced by A. tumefaciens (a polyketide/nonribosomal peptide molecule encoded by a large gene cluster of almost 53 kb) is controlled by such a factor, which we have designated I (54).…”
Section: Discussionmentioning
confidence: 99%
“…Full expression often requires the presence of the siderophore. By a variety of different mechanisms involving extracellular cytoplasmic function (ECF) sigma/anti-sigma factors, two-component regulatory systems or AraC-type regulators, the siderophore induces the expression of genes necessary for its uptake and, in certain cases, also for its biosynthesis (Poole & McKay, 2003;Visca et al, 2002). In this type of regulation, also known as siderophore-mediated signalling , perception of the siderophore can occur either at the cell surface, in the periplasm, or in the cytoplasm; examples are provided by pyoverdine-, enterobactin-and pyochelinmediated signalling in the Gram-negative bacterium Pseudomonas aeruginosa.…”
Section: Introductionmentioning
confidence: 99%